Healing Wound with Bioelectric stimulation: A Systematic Review - Nuh Huda; Farida, Imroatul; Nurhayati, Ceria; Rohman (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
This study delves into the burgeoning field of bioelectricity and its application to wound healing. A comprehensive literature analysis was conducted using Scopus, examining 831 articles published between 2014 and 2024. Keyword co-occurrence analysis through VOSviewer identified vital research themes. The findings underscore a growing interest in understanding the underlying bioelectric mechanisms that govern wound healing and the development and application of bioelectric therapies. A critical literature analysis reveals the potential of bioelectric interventions to accelerate wound closure, enhance tissue regeneration, and improve overall patient outcomes. However, significant challenges remain, such as the need for standardized protocols, the development of innovative bioelectric materials, and robust clinical evidence. This review emphasizes the importance of continued research to translate promising preclinical findings into effective clinical treatments. A deeper understanding of bioelectric signalling and its manipulation will be instrumental in developing novel therapeutic strategies for wound healing